(untitled) (Medical Forum Monthly, 2020)
Objective: To establish a probable relationship of serum testosterone with total leucocyte count and differential leucocyte count in Pakistani male population. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Institute of Basic Medical Sciences, Dow University of Health Sciences, Karachi, lasting from September 2010 to September 2011. Materials and Methods: It was conducted on 200 apparently healthy non-smoker males between 30-50 years selected by convenient sampling. Early morning samples of serum total testosterone and WBC count were obtained by phlebotomy after detailed medical history and thorough physical examination. All tests run on the same day and results were calculated. Results: The mean (±SD) total testosterone was 15.92±6.32nmol/L. The frequency of low testosterone was 13.5%. TLC and neutrophils inversely correlated with testosterone (p< 0.05) whereas lymphocytes, eosinophils and monocytes did not correlate with testosterone. Conclusion: Low testosterone is prevalent in Pakistani middle age non-smoker apparently healthy men. Significant inverse relationship of testosterone with WBC count showed that physiological variations in testosterone could modulate immune response in Pakistani men.